‘It’s not one size fits all’: a qualitative study of patients’ and healthcare professionals’ views of self-management for bronchiectasis - Kelly, Carol Ann (BMJ Open Respir Res, 2021)
BACKGROUND: Bronchiectasis is a chronic respiratory condition that impacts significantly on individuals and healthcare services. Self-management is recommended in clinical guidelines for bronchiectasis as an intervention to enable patients to manage their condition, yet there is little evidence to support it. METHODS: Three face to face focus groups (17 adults with bronchiectasis) were conducted at three National Health Service (NHS) sites in North West England. Additionally, semi-structured telephone interviews were undertaken with 11 healthcare professionals (HCPs), including doctors, nurses and physiotherapists. Thematic analysis identified common themes and occurrences verified by independent audit. FINDINGS: Four common overarching themes were identified: the meaning of self-management; benefits; barriers and influencers to self-management; subthemes varied. Both groups recognised component interventions. Patients highlighted that self-management enabled them to learn what works and moderate behaviour. Aspects of delivery and structure were important to HCPs but a ‘make do’ culture was evident. Benefits for both groups included empowering patients. Common barriers for patients were time, mood and lack of access to support which could mitigate engagement with self-management. HCPs identified barriers including patient characteristics and lack of resources. Influencers for patients were peer, carer and psychosocial support, for HCPs influencers were individual patient attributes, including ability and motivation, and HCP characteristics such as knowledge and understanding about bronchiectasis. SUMMARY: This is the first study to explore patients’ and HCPs’ views of self-management for bronchiectasis. The need for an individual, flexible and responsive self-management programme specific to bronchiectasis was evident. Personal characteristics of patients and HCPs could affect the uptake and engagement with self-management and HCPs knowledge of the disease is a recognised precursor to effective self-management. The study identified key aspects for consideration during development, delivery and sustainability of self-management programmes and findings suggest that patients’ psychosocial and socioeconomic circumstances may affect adoption and activation of self-management behaviours.